MUNICIPAL SOLID WASTE QUANTIFICATION AND CHARACTERIZATION IN BANYUWANGI, INDONESIA - Lailatus Siami; Titien Sotiyorini; Ni’matul Janah (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2019)
Aim: This study aims to identify the characteristics and generation of municipal solid waste (MSW) in Banyuwangi. Methodology and Results: The solid waste characterization was carried out in two areas in Banyuwangi, referring to the Indonesian National Standard (Standar Nasional Indonesia/SNI) 19-3964-1995. The results show that the highest composition is organics of 36% (39% from households/HSW and 35.35% from Non-HSW). The highest solid waste (SW) generation from industrial areas and train station are 0.61 and 1.38 kg/population.day, respectively, while the SW density from the bus station is 375.46 kg/m3. The weight, volume, and density of household solid waste (HSW) are 0.17 kg/population.day, 2.02 L/population.day, and 81.07 kg/m3, respectively. The population of Zone 1 and Zone 2 is 142.054 in 2016, generating 8,814 tons of HSW per year (tpy). Conclusion, significance and impact study: The main MSW compositions in Banyuwangi are organics (36%), plastics (17.20%), and papers (15.78%). Household solid waste generation in Banyuwangi reaches 8.8 tons per year with the primary compositions of 39% organics, 18.92% residues, 18.4% papers, and 14.4% plastics. The highest number of residue defines that 81% of solid waste can be recycled.